Holocene dynamics of the southern westerly winds over the Indian Ocean inferred from a peat dust deposition record. (1st March 2020) - Li, Chuxian; Sonke, Jeroen E.; Le Roux, Gaël; Van der Putten, Nathalie; Piotrowska, Natalia; Jeandel, Catherine; Mattielli, Nadine; Benoit, Mathieu; Wiggs, Giles F.S.; De Vleeschouwer, François
Abstract: The southern westerly winds (SWW) play a major role in climate variability in Southern Hemisphere mid- and high-latitudes, regulating rainfall, ocean circulation, and the Southern Ocean carbon sink. Despite their importance, little is known about millennial scale changes in the SWW and how they have influenced the climate system in the past and interacted with the Earth's surface elements, such as dust, nutrients and carbon. Here we present a dust record from a 6.6 kyr old peat core in Amsterdam Island (AMS) situated at the northern edge of the SWW (37°S) in the Southern Indian Ocean. Mineral dust flux was used to track atmospheric dust production, long-distance transport and subsequent deposition. Dust provenance was determined from rare earth element (REE) and Nd isotopic signatures (εNd) in the peat core, compared with a reference dataset of Southern Hemisphere dust sources. Using a multi-proxy mixing model, the εNd and REE ratios show a relatively uniform mixture of ca. 40% local, 15% Southern African and 45% Southern South American dust sources since 6.6 cal kyr BP. However, from 1910 AD onwards, there is a doubling in the contribution from Southern Africa (32%). Two mineral dust flux minima occur at 6.2–4.9 cal kyr BP and 3.9–2.7 cal kyr BP, interpreted as periods with equatorward-shifted and/or strengthened SWW at the northern edge of the wind belt. Conversely, periods of higher dust flux at 6.6–6.2 cal kyr BP, 4.9–3.9 cal kyr BP, and 1.4 cal kyr BP onwards are interpreted as poleward-shifted and/or weakened SWW. These interpretations are based on the findings that higher (lower) wind speeds lead to enhanced (less) removal of distal dust on the way to AMS, by wet deposition and turbulence. Published Holocene SWW records at the northern edge of the wind belt (33–41°S) covering South-America, Southern-Africa and Australia, show much variability over the last 6.6 kyr. We suggest this reflects complex regional climate variability in the different SH longitudinal sectors, indicating that SWW are not zonally homogeneous at the northern edge of the wind belt. The recent shift in dust provenance is not accompanied by enhanced total dust deposition at AMS. We therefore suggest that human impact (e.g., land use changes) and drier climate conditions in Southern Africa have led to enhanced dust mobilization. Highlights: Amsterdam Island peat εNd and REE ratios indicate 40% local dust input, 15% Southern Africa and 45% Southern South America from 6.6 kyr cal BP to 1910AD. Low mineral dust deposition to the peatland at 6.2–4.9 and 3.9–2.7 cal kyr BP suggests an equatorward-shifted and/or strengthened SWW at their northern edge. Enhanced Southern African dust mobilization during the last 100 years is likely related to anthropogenic changes in land-use and the drier climate conditions.